Pengaruh Permainan Puzzle terhadap Perkembangan Kognitif Anak di KB Hidayatul Mubtadi’in Rembang - M Mujib Utsmani; Nova Auliyatul Faizah (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2020)
This study aims to apply and find out the improvement of cognitive abilities in the method of playing puzzles. This type of research is classroom action research. The results of the study are as follows: There is an increase in cognitive abilities in the method of playing puzzles. This can be seen from the results of completeness of children's learning at the pre-cycle stage of children's cognitive development achievements in sorting puzzle pieces unfinished. Based on the research results of children's learning completeness in the first cycle phase of 46.15% with the criteria of Not Developing (BB) for an average of 63.46 with sufficient criteria, the second cycle of learning completeness by 84.6% with the criteria of Developing in Accordance with Expectations (BSH) for an average of 80.38 with Good criteria. Then it can be concluded that the impact of using the method of playing puzzles makes it easy for children to complete tasks and increase enthusiasm for learning.